AIAA Guidance, Navigation, and Control Conference and Exhibit 2006
DOI: 10.2514/6.2006-6777
|View full text |Cite
|
Sign up to set email alerts
|

An L1 Adaptive Pitch Controller for Miniature Air Vehicles

Abstract: One of the challenges in designing low level control loops for Micro Air Vehicles (MAVs) is that the manufacturing process for airframes is not consistent enough to ensure uniform aerodynamic properties. Therefore, there is a significant need for robust adaptive control techniques that are computationally simple. Conventional Model Reference Adaptive Controllers (MRAC) have proved to be very useful in a number of flight tests over the past years. However, a major drawback of this control architecture is that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Unlike conventional adaptive controllers, the L 1 adaptive controllers adapt fast, leading to desired transient and asymptotic tracking with a guaranteed, bounded away from zero, time-delay margin [27]. The results from [5,6] have been intensively applied in flight tests [11,[28][29][30][31] and various mid-to high-fidelity simulation environments [32][33][34][35]. Insights into the performance of L 1 adaptive controller can be obtained from the analysis of a simple linear system in [36], in which sensitivity and cosensitivity transfer functions are analyzed for disturbance rejection and noise tolerance in the presence of a large adaptation rate.…”
Section: Introductionmentioning
confidence: 98%
“…Unlike conventional adaptive controllers, the L 1 adaptive controllers adapt fast, leading to desired transient and asymptotic tracking with a guaranteed, bounded away from zero, time-delay margin [27]. The results from [5,6] have been intensively applied in flight tests [11,[28][29][30][31] and various mid-to high-fidelity simulation environments [32][33][34][35]. Insights into the performance of L 1 adaptive controller can be obtained from the analysis of a simple linear system in [36], in which sensitivity and cosensitivity transfer functions are analyzed for disturbance rejection and noise tolerance in the presence of a large adaptation rate.…”
Section: Introductionmentioning
confidence: 98%
“…Flight control has long been a privileged applicative field for robust and gain-scheduling control, see, eg, previous works [1][2][3][4][5][6] and more recently, for fault-tolerant and adaptive control. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Noting that strong links exist between all these fields. Indeed, robust and adaptive control can be seen as competing/complementary techniques for solving the same problem of controlling an uncertain plant.…”
Section: Introductionmentioning
confidence: 99%
“…24 Nevertheless, a physical aerodynamic state-space model is available for an aircraft (A/C), and state-space methods are typically used to design robust or gain-scheduled flight control laws so that adaptive flight controllers are usually designed using state-space methods, see, eg, previous works. 8,[10][11][12][13][14][15][16][18][19][20][21][22] Generally speaking, 2 main problems need to be solved in adaptive control, namely, to obtain a priori guaranteed stability and performance properties of the adaptive closed loop and to decrease the online computational time and complexity. In the context of indirect adaptive control, following the works of Ferreres and Antoinette, 25,26 a solution based on robust and gain-scheduled control tools is to design off-line a gain-scheduled controller, depending on the plant parameters to be estimated, to avoid the complexity of implementing a control design algorithm online.…”
Section: Introductionmentioning
confidence: 99%
“…The MRAC controller was tested for the uncertainty in aerodynamic coefficients by deploying the flap during flight tests. Beard et al [7] used a L1 adaptive algorithm to control the pitch attitude loop for MAVs. Simulation and flight test showed that L1 adaptive controller exhibited robustness for variable sample rates, as well as for time delays.…”
Section: Introductionmentioning
confidence: 99%